Income contingent loans in higher education financing - Bruce Chapman (IZA World of Labor, 2016)
Around nine countries currently use a national income contingent loan (ICL) scheme for higher education tuition using the income tax system. Increased international interest in ICL validates an examination of its costs and benefits relative to the traditional financing system, government-guaranteed bank loans (GGBLs). Bank-type loans exhibit poor economic characteristics: namely, repayment hardships for the disadvantaged, and default. This damages credit reputations and can be associated with high taxpayer subsidies. ICLs avoid these problems, but effective collection of debt requires a sophisticated mechanism.
Keywords: I20; I21; I22; I23; I28; H42; 330; income contingent loans; government-guaranteed bank loans; consumption smoothing; default insurance; repayment burdens